User Acceptance of RFID Technology Application in the Retail Industry - Xiao, Jing (2013)
RFID technology as highly praised as the next wave of innovative technology, using RFID technology in the retail industry can help the organization satisfy customer demand, reduce management cost and increase the efficiency of product flows. While most of businesses still do not want to use RFID technology in their organization and the drivers of user acceptance of RFID technology remain unclear because the RFID technology has seldom been tested in the retail industry. This study is to identify the factors which can influence the acceptance of RFID technology in the retail industry. The quantitative survey was completed by 85 employees in the retail industry in Nilai. The survey included measures of eight main factors of acceptance of RFID technology through literature review: perceived ease of use (PEOU), perceived usefulness (PU), relative advantage (RA), compatibility (CA), complexity (CL), cost saving (CS), organizational context (O) and environmental content (E). Results were obtained through reliability test, validity test and correlation analysis. Results obtained that perceived ease of use (PEOU), perceived usefulness (PU), relative advantage (RA), compatibility (CA), cost saving (CS) and organizational context (O) has positively influence on acceptance of RFID technology.